2016
DOI: 10.1007/s11999-015-4639-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Surgical Approach Affect Patient-reported Function After Primary THA?

Abstract: Background Total hip arthroplasty (THA) relieves pain and improves physical function in patients with hip osteoarthritis, but requires a year or more for full postoperative recovery. Proponents of intermuscular surgical approaches believe that the direct-anterior approach may restore physical function more quickly than transgluteal approaches, perhaps because of diminished muscle trauma. To evaluate this, we compared patient-reported physical function and other outcome metrics during the first year after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 48 publications
5
69
0
5
Order By: Relevance
“…7,27 Rathod et al published a similar study in 2014 comparing radiographic outcomes between the DAA with intra-operative fluoroscopy and the posterior approach and found results similar to ours with regard to acetabular inclination. They did not compare offset or LLD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7,27 Rathod et al published a similar study in 2014 comparing radiographic outcomes between the DAA with intra-operative fluoroscopy and the posterior approach and found results similar to ours with regard to acetabular inclination. They did not compare offset or LLD.…”
Section: Discussionsupporting
confidence: 81%
“…1 Several studies have demonstrated benefits of the DAA, including decreased narcotic consumption, more soft tissue and muscle preservation, faster recovery, shorter hospital stay, improved restoration of gait mechanics, and decreased dislocation rate. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Many authors claim that this approach would result in less muscle damage and rapid recovery, although only limited data exist to support these claims [34][35][36]. Nevertheless, any attempt to decrease pain, blood loss and recovery time may be a benefit for the patient, which would enable a quick return to daily routine.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in which it could be shown that after hip arthroplasty, the patients improved significantly measured by scores like Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Harris Hip Score (HHS) in a short and long term [1, 2]. Several studies could show good results after minimal invasive THA in the early postoperative period measured by HHS and WOMAC [35]. …”
Section: Introductionmentioning
confidence: 99%